Pan-Cancer Analysis of OLFML2B Expression and Its Association With Prognosis and Immune Infiltration - Hu, Pengbo; Zhang, Xiuyuan; Li, Yiming; Xu, Liang; Qiu, Hong (Frontiers in Genetics, 2022)
Background: The function of olfactomedin-like 2B (OLFML2B), as a member of the olfactomedin domain-containing proteins family, is remain ambiguous especially in tumors. In the current study, we aimed to explore possible correlation among OLFML2B, prognosis and immune infiltration in pan-cancer. Methods: We applied a train of bioinformatics techniques to probe the prospective function of OLFML2B, consisting of its association of prognosis, clinicopathology, alteration, GSEA, tumor microenvironment (TME), immune associated genes, immune infiltration, tumor mutational burden (TMB), microsatellite instability (MSI) and drug sensitivity in several cancer types. qPCR was used to identified OLFML2B expression in LIHC cell lines. Results: We discovered that OLFML2B is over-expressed in 14 cancers and is positively related to prognosis of several cancer types. The expression of OLFML2B was further validated in LIHC cell lines. OLFML2B expression is bound up with TMB in 13 cancers, MSI in 10 cancers and TME in almost all cancers. Furthermore, OLFML2B is highly co-expressed with genes encoding MHC, chemokines, chemokine receptors, immune activators and immune suppressors. We further found that OLFML2B plays a role in the infiltration of different types of immune cells, such as macrophages and cancer associated fibroblasts. OLFML2B may latently influence various important cancer and immune related pathways, such as PI3K-Akt signaling pathway, ECM-receptor interaction, focal adhesion and leukocyte transendothelial migration. Besides, OLFML2B may increase drug resistance of binimetinib, Cobimentinib, Trametinib. Conclusion: Our outcomes reveal that OLFML2B may act as a prognostic marker and a potential target in immunotherapy for diverse tumors owing to its function in oncogenesis and immune infiltration.